Investigating the Role of School Principals in Creating a Harmonious 3R+1R Learning Environment - Ong, Puay Tee; Ong, Puay Hoon; Ong, Puay Liu; Ting, Helen; Paul, Porodong (Elsevier Ltd., 2010)
This paper presents a relatively new approach to investigate the Principals’ leadership behaviours. Qualitative data gathered through interviews with Principals from eight secondary schools (four urban and four rural) in Sabah and Sarawak will be collated and mapped against Jack Welch’s typology of leadership (Bryne, 1998; Shanley, 2005), namely “E to the fourth power” leadership model. This typology serves as a dynamic way for obtaining insights into principals who occupy the apex of leadership and management in the school’s social system. The leadership behaviours will be mapped against school performance. Results and findings will be discussed.